Análise dos dados de ciclo de transporte gerados pelo sistema de despacho para uma mina de cobre - Aline Lorraine Silva Lacerda (2019)
Dispatch system is a fleet management solution that allows a mine operation to maximize production and efficiency, while minimizing operational costs through assignments based on real-time data. In order to permit the system to reach for the optimal solution and generate real operational data, it’s necessary to assure data accuracy and quality, basis for the optimization algorithm account. In addition, collected data from a dispatch database system is essential to support operational reports and thus demand trustworthy information for key business management. Regular monitoring of load and haul cycles coupled with continual analysis of dispatch reports provides opportunity to identify operational improvement, showing several cases for improvement to cycle times in the Sossego operation. This study aims to analyze and characterize the integrity of data collected in real time by the dispatch system at Sossego Mine by using the continuous improvement methodology Lean Six Sigma, in order to assure an optimized operation and accurate data generate by the system.